MECHANICAL CHARACTERISTICS OF STEEL FIBER CONCRETE REINFORCED WITH FIBER OF NE1050 TYPE UNDER SHORT-TERM COMPRESSION - Bidenko, І. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
The article studies the influence of the coefficient of fiber reinforcement by volume ρ_fv when using steel fiber of the NE1050 type with bent ends of Ukrainian production on the strength and deformability of dispersed-reinforced concrete under short-term compression, and makes proposals for calculating the strength and analytical description of the corresponding deformation diagram. According to the research program, the strength of fine-grained concrete is assumed to be of C20/25 and C30/35 classes, which are most often used in the structures without prestressing the core reinforcement; the percentages of fiber reinforcement by volume are 0 %, 0.7 %, 1.25 %; 1.8 %, since at lower percentages of fiber reinforcement, its effect may not be observed, and at higher percentages, the structures cease to be competitive. The strength and deformation characteristics of steel fiber concrete were studied on compressed prism specimens of 100 × 100 × 400 mm. To produce prisms of C20/25 class concrete, the following composition was adopted: M400 cement with an activity of 41.2 MPa – 445 kg, sand with a modulus of 2.1 – 1645 kg, and water – 240 liters. To obtain C30/35 class concrete, the following composition was adopted, particularly M500 cement with an activity of 52.3 MPa – 431 kg, sand with a particle size modulus of 2.1 – 1724 kg, and water – 216 liters. The fiber consumption per 1 m3 was 54.95, 98.13, and 141.3 kg at the percentages of reinforcement of 0.7, 1.25, and 1.8, respectively. It is shown that an increase in the coefficient of fiber reinforcement by volume contributes to an increase in the strength of steel fiber concrete, relative deformations corresponding to the peak point of the deformation diagram, the initial modulus of elasticity of steel fiber concrete, and a decrease in relative deformations at a specific stress level. The research confirms the expediency of using a modified formula of norms in the form of a fifth-degree polynomial to describe the deformation diagram of steel fiber concrete under short-term compression and determines the coefficients of this polynomial.